Bank soundness level impact on stock prices: Risk, governance, income, capital measurement.: Pengaruh Profil Risiko, Tata Kelola Perusahaan yang Baik, Pendapatan, dan Modal sebagai Pengukuran Tingkat Kesehatan Bank terhadap Harga Saham - Rita Irma Suryani Nasution; Heri Widodo (Academia Open, 2022)
This study aims to prove and analyze the influence of Risk Profile, Good Corporate Governance, Earnings, and Capital as measured through 4 variables, namely non-performing loan, good corporate governance, net interest margin, capital adequacy ratio to stock prices. This study used Islamic commercial bank companies in 2015-2019 as its population with the total number of companies being 13 companies. The sample is selected using the purposive sampling method. The study used a quantitative approach and tested research data using SPSS regression program data. From the results of calculations, it was concluded that non-performing loans, net interest margin, capital adequacy ratio has an influence on stock prices. Good corporate governance has no effect on stock prices. Highlights: The study analyzes the impact of risk profile, governance, earnings, and capital on stock prices. Non-performing loans, net interest margin, and capital adequacy ratio affect stock prices. Good corporate governance does not have a significant impact on stock prices. Keywords: Risk Profile, Good Corporate Governance, Earnings, Capital, Stock Prices.